Picture books and imagination: writers, illustrators and readers in an interactive connection - Anelise Zimmermann; Neli Klix Freitas (Universidade Federal de Santa Catarina, 2018)
The objective of this article is to establish some relationships between picture books for children and the exercise of imagination, considering the experiences of writers, illustrators, and readers. These relationships are established based on Vygotsky's perspective on imagination, considering its essential role in mediating the world and humans in a complex interaction. According to Vygotsky, humans' experiences and emotions are the raw material for the imagination, while the practice of imagining expands human's interactions with the world. In this light, picture books for children can be considered element of mediation in this process. This study analyses interviews with writers, illustrators, and readers in which they talk about their relations with books, their creative process, and imagination. Finally, the reflections generated corroborate the relevance of picture books not only to childhood but throughout the life of readers as individuals who interact with others, and shape and transform the world.